2020
DOI: 10.4414/smw.2020.20193
|View full text |Cite
|
Sign up to set email alerts
|

Should systemic sclerosis be recognised as an occupational disease in Switzerland?

Abstract: Systemic sclerosis is a rare autoimmune disease characterised by a multifactorial aetiology involving a gene-environment interaction. Despite the growing epidemiological arguments for odds ratio (OR) data showing an association with occupational exposure, systemic sclerosis is not currently included in the list of recognised occupational diseases in Switzerland, unlike other northern European countries. Future recognition will be conditional on the demonstration of a strong association between the disease and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Pesticides increased the risk of SSc in females by an OR > 3 in contrast to males, who did not show an increased risk. 2…”
Section: Environmental Factors As Important Contributors For Sscmentioning
confidence: 99%
See 2 more Smart Citations
“…Pesticides increased the risk of SSc in females by an OR > 3 in contrast to males, who did not show an increased risk. 2…”
Section: Environmental Factors As Important Contributors For Sscmentioning
confidence: 99%
“…1 Epidemiological studies of SSc identified strong associations with occupational factors such as exposure to silica and solvents with odds ratios (ORs) > 2 and weaker associations with epoxy resins and welding fumes. 2 Interestingly, sex is an influencing factor to be considered in the increase of risk for SSc. For example, exposure to silica increased the risk of SSc by an OR > 3 in males, while it was lower in females.…”
Section: Environmental Factors As Important Contributors For Sscmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common occupational exposure is to silica dust, which induces silicosis, rheumatoid arthritis and lung cancer; the association of silicosis with SSc or mixed connective tissue disease, known under the name of Erasmus syndrome, has also been considered for inclusion in the occupational diseases category. Researchers suggest that SSc associated with silica dust exposure should be included in the occupational diseases category, even when silicosis is not present (17,18). Silicon dioxide nanoparticles (nano-SiO 2 ) in their amorphous state are microparticles with a diameter of less than 100 nm and a very low density, which can easily become airborne and inhaled.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al also revealed the significant exposure to ketones (18). Recent studies show that epoxy resins, which are included in the list of occupational toxins, may be involved in the onset of SSc (17,18,20). Not only occupational exposure to toxins poses a risk, but also constant or accidental pollution through water and air contamination with halogenated compounds and aromatic hydrocarbons, such as benzene, xylene and toluene (21).…”
Section: Introductionmentioning
confidence: 99%